Bibliometric analysis of nicotinic acetylcholine receptors channel research (2000-2020). Issue 1 (1st January 2021) - Zhu, Xueping; Zhou, Yan; Yuan, Guozhen; Shi, Jingjing; Shi, Shuai; Zhang, Limei; Chai, Ruoning; Du, Yihang; Duan, Chenglin; Hu, Yuanhui
ABSTRACT: To explore the research status, hotspots, and trends in research on nicotinic acetylcholine receptor (nAChR) channel. The Web of Science core collection database from 2000 to 2020 was used as the data source. The visual analysis software VOSviewer1.6.16 and Citespace5.7 R3 were used to visualize the studies of the nAChR channel. The national/institutional distribution, journal distribution, authors, and related research were discussed. A total of 5, 794 articles were obtained. The USA and the Utah System of Higher Education were the most productive country and institution for nAChR channel research. Journal of Biological Chemistry was the most productive journal (212) and the most productive researcher was McIntosh, J. Michael. The first highly co-cited article was "Refined structure of the nicotinic acetylcholine receptor at 4A resolution." The most researched area was neurosciences neurology. The hot spots of nAChR channel research were "subunit and structure of nAChR, " "activation/agonist of nAChR channel, " and "Changes in nAChRs With Alzheimer's Disease." The top three research frontiers of nAChR channel research were "neuropathic pain, " "neuroinflammation, " and "α7 nACHR." The study provides a perspective to visualize and analyze hotspots and emerging trends in the nAChR channel.